The Impact of Rice Imports on The Welfare of Local Farmers: An Islamic Economic Ethics Perspektif (2023 – 2025) - Ainol Yaqin; Nur Wahidatul Istiqomah; Azizi Abu Bakar (ARBITRASE: Journal of Economics and Accounting, 2026)
This study analyses the impact of rice import policies on the welfare of local farmers in East Java from the perspective of Islamic economic ethics. As a national rice barn province, East Java faces a paradox between increasing productivity and economic pressure due to massive rice imports. Using a descriptive qualitative approach with case studies and systematic literature review, this research finds that rice imports aimed at stabilizing national prices actually suppress grain prices at the farm level, erode income, and create unfair competition between local and imported rice. Data shows that although East Java's rice production increased in 2023-2025, the national import volume reaching 4.52 million tons in 2024 significantly impacted the decline in farmers' bargaining power. From the perspective of Islamic economic ethics, this policy is evaluated based on the principles of justice (al-'adl), benefit (maslahah), and the prohibition of causing harm (la dharar wa la dhirar). The results of normative analysis indicate that rice import policies potentially contradict Islamic values when they neglect protection for farmers as a vulnerable group and guardians of food security. This study recommends the need for import policies oriented toward balance between national price stability and distributive justice, with strengthening state intervention through fair government purchase prices and import restrictions during the main harvest season.